Analisis Kecepatan Switching IC TTL AOI Terhadap Nilai Optimal Karakteristik Bf - Syaiful Rachman; Saberan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
This study analyzes the speed of propagation time performance capabilities of the integrated circuit type of standard Dual 3-Wide 3-Input TTL IC AOI on the characteristic levels of forward common emitter current gain (βf). Simulation is carried out using SPICE software with capacitor load (CL) of 15 pf and levels of forward common emitter current gain (βf) are 5, 10, and 15. The simulation results show that tPLH (transition low to high), tPHL (transitions high to low), and mean time propagation produced differ for each βf. A propagation time of 1.59ns is obtained for βf of 5, slower than βf performance of 10, which is 1.53ns. Furthermore, βf performance with a value of 15 is 1.50ns, faster than others’. But this βf has greater power dissipation, which is 29 mW. Power dissipation produced by βf of 10 is 27 mW, and βf of 5 produced 26 mW. Therefore, IC designing must consider the characteristic level of the forward common emitter current gain (βf) value. Higher βf values produce larger power dissipation.